Translation, book history and the transnational life of "street literature". Issue 3 (2nd September 2019) - Colombo, Alice
ABSTRACT: Translation studies has exposed the transnational dimension of literature by thoroughly investigating translation as a vehicle for cross-cultural textual transmission and for the formation of internationally shared literary repertoires. So far, investigations have largely been restricted to literature in the traditional book form. This article stresses that ephemeral street literature in the chapbook and broadside format also has an interesting transnational life and proposes the complementarity between the histories of translation and of the book as an optimal framework for exploring it. The article's rationale is underpinned by the assumption that research into translated street literature can lead to more accurate representations of the cross-cultural life of printed matter, as well as of translational practices and relations.